Evaluasi Kualitas Platform Marketplace BUMDesa Menggunakan Metode Grey-Box Testing berbasis Standar ISO/IEC 9126 - Dinda Maylan Setianti; Ariq Cahya Wardhana (Bulletin of Computer Science Research, 2025)
The BUMDesa marketplace platform was developed to support the digitalization of village business processes, enhance local economic activities, and strengthen the role of BUMDesa in managing community-based enterprises. Although the platform has been utilized by several user categories, a comprehensive evaluation of its software quality has not yet been conducted. This study aims to assess the quality of the BUMDesa marketplace platform using the grey-box testing method integrated with the ISO/IEC 9126 standard. The grey-box testing approach was employed to examine both internal and external system behaviors across three platforms: the website, Android mobile application, and API. Quality evaluation was carried out based on five ISO/IEC 9126 aspects: functionality, reliability, efficiency, maintainability, and portability. The results show that the functionality aspect achieved a feasibility score of 73% (“Fair”), reliability reached 86% (“Good”), efficiency obtained 100% (“Very Good”), maintainability scored 62% (“Poor”), and portability achieved 100% (“Very Good”). These findings indicate that the platform meets quality standards in terms of reliability, efficiency, and portability, while improvements are still needed in functionality and maintainability. This study provides recommendations for enhancing software quality and may serve as a reference for evaluating similar digital platforms within village-owned enterprises.